A Systematic Review of Foreign Language Listening Anxiety: Focus on the Theoretical Definitions and Measurements - Ji, Suhe; Qin, Xiaoqing; LI, Ke (Frontiers in Psychology, 2022)
Foreign language (FL) listening anxiety, as one of the influential skill-based anxieties in FL learning, is associated with the success or failure of FL listening comprehension. A considerable amount of research on FL listening anxiety has emerged since 1986. However, a lack of sufficient attention on the conceptual definitions of FL listening anxiety and inappropriate employment of instruments to measure FL listening anxiety cause confusion in the research to a certain extent. This study presents a systematic review of 35 years of FL listening anxiety research. After initially searching 2172 studies in 7 databases, 76 studies were identified for in-depth analysis. The results verified that the definitions of FL listening anxiety can be categorized into psychological, social, and situation-specific approaches, but the measure of FL listening anxiety was not only examined under these three approaches, but also additionally examined by sources of anxiety, learner characteristics, FL listening ability, and physiological factors. The results also revealed that the definition of FL listening anxiety was not clear-cut nor that the measure was accurate, and to a great extent the measure and the definition were inconsistent. This inconsistency can attribute to conceptual fuzziness in theoretical defining and casual utilization of scales without justification or explanation. We argue that future research needs to provide a tighter link between a more precise definition based on different situations and a valid measure of FL listening anxiety.